Osteoarthritic Synovial Fluid and TGF-β1 Induce Interleukin-18 in Articular Chondrocytes. (July 2020) - Carballo, Camila B.; Coelho, Thiago R. P.; de Holanda Afonso, Rosenilde C.; Faria, Jane Cristina de Oliveira; Alves, Tercia; Monte, Samylla M.; Ventura Matioszek, Grasiella M.; Moura-Neto, Vivaldo; Brito, José M. de
Objective: Synovial fluid (SF) plays an important role in the maintenance of articular cartilage. SF is a dynamic reservoir of proteins derived from cartilage and synovial tissue; thus, its composition may serve as a biomarker that reflects the health and pathophysiological condition of the joint. The purpose of the current study was to evaluate the osteoarthritic synovial fluid (OASF) and transforming growth factor-β1 (TGF-β1) activity in articular chondrocytes catabolic and inflammatory responses. Design: Chondrocytes were seeded at passage 2 and cultured for 72 hours under different conditions. Human chondrocytes were subjected to OASF while rat chondrocytes were subjected to either healthy synovial fluid (rSF) or TGF-β1 and then assigned for cell viability analysis. In addition, the effects of OASF and TGF-β1 on chondrocytes metalloprotease (MMP)-3 and MMP-13 and interleukin-18 (IL-18) expression were evaluated by immunocytochemistry, ELISA, and reverse transcriptase-polymerase chain reaction. Results: SF from osteoarthritic patients significantly induced MMP-3, MMP-13, and IL-18 receptor expression in chondrocytes. To put in evidence the inflammatory activity of OASF, healthy chondrocytes from rat were cultured with TGF-β1. In the presence of TGF-β1 these cells started to express MMP-3, MMP-13, and IL-18 genes and attached to each other forming a chondrocyte aggregated structure. Healthy SF was able to maintain a typical monolayer of rounded chondrocytes with no inflammatory response. Conclusion: In summary, these observations demonstrated that TGF-β1, one of the components of OASF, has a dual effect, acting in chondrocyte maintenance and also inducing inflammatory and catabolic properties of these cells.